Kinematic Modelling of FES Induced Sit-to-stand Movement in Paraplegia - Mohammed Ahmed; M. S. Huq; B. S. K. K. Ibrahim (International Journal of Electrical and Computer Engineering (IJECE), 2017)
FES induced movements from indication is promising due to encouraging results being obtained by scholars. The kinematic model usually constitute the initial phase towards achieving the segmental dynamics of any rigid body system. It can be used to ascertain that the model is capable of achieving the desired goal. The dynamic model builds on the kinematic model and is usually mathematically cumbersome depending on the number of degrees-of-freedom. This paper presents a kinematic model applicable for human sit-to-stand movement scenario that will be used to obtain the dynamic model the FES induced movement in a later study. The study shows that the 6 DOF conceptualized sit-to-stand movement can be achieved conveniently using 4 DOF. The 4 DOF has an additional joint compared to similar earlier works which makes more it accurate and flexible. It is more accurate in the sense that it accommodates additional joint i.e. the neck joint whose dynamics could be captured. And more flexible in the sense that if future research uncover more contributions by the segments it can be easily incorporated including that of other segments e.g. the trunk, neck and upper limbs.